Evaluation of the profile of cytopathological examinations of the cervix in Brazil: a descriptive study (Research, Society and Development, 2023)
Objective: To evaluate the epidemiological profile of cytopathological examination and its main changes carried out in Brazil in the last 5 years. Methods: This is a quantitative descriptive epidemiological study, in which data were obtained through the Cancer Information System (SISCAN) between 2017 and 2022. Results: During the period studied, 37,020,409 cytopathological examinations of the cervix were performed in the Brazil. With regard to age, approximately 90% of the exams were in the recommended age group for cervical cancer screening, with emphasis on the drop of approximately 44% in the number of cytopathological exams performed in 2020, making it possible to correlate with the period of the pandemic by SARS- CoV-2. Most of the exams evaluated (85%) showed some benign or malignant alteration, however, only 2.9% had alterations, after excluding benign ones. Conclusion: Most alterations in the cytopathological exams were benign, whereas the malignant ones presented a similar prevalence to those in the literature, with squamous cell carcinoma being more common, followed by adenocarcinoma.